Is It Still Possible to Collect Nationally Representative Marriage Data in the United States? A Case Study From the CREATE Project. Issue 4 (21st September 2021) - James, Spencer L.; Yorgason, Jeremy B.; Holmes, Erin K.; Johnson, David R.; Busby, Dean M.
Abstract : Objective: To understand challenges in the data collection environment for collecting nationally representative data and discuss one study's response to these challenges. Background: The United States is undergoing impressive and transformational social change related to marriage. Social scientists' ability to study such changes are contingent on being able to minimize sampling error (the difference between the sample and the population), accomplished most reliably by collecting representative survey data and making concomitant generalizations from them. Given the expected low response rates in contemporary survey research, it is natural to ask whether it is still possible to collect high‐quality, nationally representative survey data on marriage and family. Method and Results: This article presents an argument about the importance of continuing to collect nationally representative data on marriages and families, a discussion about the challenges associated with the task, an example of how one project managed and dealt with that environment, and data comparisons between multiple sampling methods. Conclusion: Despite the challenges, scholars must continue to pursue nationally representative data to inform knowledge of national trends and relationships. Implications: A greater focus on sampling methods and a study's concomitant generalizability and external validity will improve knowledge of trends in marriage and family relationships, leading to improved therapeutic practice; more informed policymaking; and better theoretical, conceptual, and methodological understanding of key family processes and outcomes.